2013
DOI: 10.4236/ojped.2013.33050
|View full text |Cite
|
Sign up to set email alerts
|

Causes of developmental delay in children of 5 to 72 months old at the child neurology unit of Yaounde Gynaeco-Obstetric and Paediatric Hospital (Cameroon)

Abstract: Background: According to the World Health Organization, about 5% of children world-wide of 14-year-old and under have a moderate to severe developmental disability, and up to 15% of children under 5-year-old are developmentally delayed. Purpose: To determine the prevalence, socio-demographic profile, aetiologies, and the clinical presentation of developmental delay in children less than 6-year-old at the child neurology unit in a university-affiliated hospital in Yaounde. Materials and methods: It was a crosss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 20 publications
4
14
1
Order By: Relevance
“…Few studies, Nguefack et al, and Meliegy et al, had high proportions of birth asphyxias similar to ours as a cause of developmental delay. 9,10 Nguefack et al, had 68 (44.40%) children with history of birth asphyxia similar to the present study as a leading cause of developmental delay. 9 Most of the studies found etiology of birth asphyxia to be around 9 -23% in children with developmental delay in their studies, and birth asphyxia was taken as an important predictor of developmental delay.…”
Section: Birth Asphyxiasupporting
confidence: 87%
See 2 more Smart Citations
“…Few studies, Nguefack et al, and Meliegy et al, had high proportions of birth asphyxias similar to ours as a cause of developmental delay. 9,10 Nguefack et al, had 68 (44.40%) children with history of birth asphyxia similar to the present study as a leading cause of developmental delay. 9 Most of the studies found etiology of birth asphyxia to be around 9 -23% in children with developmental delay in their studies, and birth asphyxia was taken as an important predictor of developmental delay.…”
Section: Birth Asphyxiasupporting
confidence: 87%
“…9,10 Nguefack et al, had 68 (44.40%) children with history of birth asphyxia similar to the present study as a leading cause of developmental delay. 9 Most of the studies found etiology of birth asphyxia to be around 9 -23% in children with developmental delay in their studies, and birth asphyxia was taken as an important predictor of developmental delay. Some Indian studies by Jain et al, Tikaria et al, and Sachdeva et al, found birth asphyxia in 9.8%, 20%, and 9% of children enrolled in their studies respectively which are lower than our study.…”
Section: Birth Asphyxiasupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, Nguefack et al in 2013 stated that perinatal asphyxia was the most frequent perinatal factor to cause developmental delay (44%; P=0.05). 12 Perinatal hypoxia-ischemia is responsible for primary and secondary cerebral energy failure, a phenomena in which the blood flow to the brain is decreased, thus reducing oxygen transport. These phenomena are also responsible for decreased highenergy phosphorylated compounds.…”
Section: Discussionmentioning
confidence: 99%
“…In Cameroon, BMs are often discovered during investigation for epilepsy or psychomotor retardation [13] Open Journal of Medical Imaging [14]. MRI has been recently introduced and the CT scan was previously the reference technique for the diagnosis of BM in our context.…”
Section: Introductionmentioning
confidence: 99%